2017
DOI: 10.1534/genetics.117.1124
|View full text |Cite
|
Sign up to set email alerts
|

The Stress-Sensing TORC2 Complex Activates Yeast AGC-Family Protein Kinase Ypk1 at Multiple Novel Sites

Abstract: Yeast (Saccharomyces cerevisiae) target of rapamycin (TOR) complex 2 (TORC2) is a multi-subunit plasma membrane-associated protein kinase and vital growth regulator. Its essential functions are exerted via phosphorylation and stimulation of downstream protein kinase Ypk1 (and its paralog Ypk2). Ypk1 phosphorylates multiple substrates to regulate plasma membrane lipid and protein composition. Ypk1 function requires phosphorylation of Thr504 in its activation loop by eisosome-associated Pkh1 (and its paralog Pkh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
55
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 33 publications
(58 citation statements)
references
References 83 publications
3
55
0
Order By: Relevance
“…Strikingly, however, even though Avo2 is nonessential for cell viability under nonstress conditions, we found that Avo2 is essential for cell survival during myriocin-induced sphingolipid depletion (Fig. 2B, top row), a condition in which cells require full TORC2-mediated activation of Ypk1 to survive (Roelants et al 2011;Leskoske et al 2017). Furthermore, compared with cells expressing wild-type Avo2 or Avo2 9A , cells expressing Avo2 9E were much more sensitive to the growth inhibitory effect of myriocin ( Fig.…”
Section: Mapk Phosphorylation Of Avo2 Impairs Torc2 Activitymentioning
confidence: 84%
See 1 more Smart Citation
“…Strikingly, however, even though Avo2 is nonessential for cell viability under nonstress conditions, we found that Avo2 is essential for cell survival during myriocin-induced sphingolipid depletion (Fig. 2B, top row), a condition in which cells require full TORC2-mediated activation of Ypk1 to survive (Roelants et al 2011;Leskoske et al 2017). Furthermore, compared with cells expressing wild-type Avo2 or Avo2 9A , cells expressing Avo2 9E were much more sensitive to the growth inhibitory effect of myriocin ( Fig.…”
Section: Mapk Phosphorylation Of Avo2 Impairs Torc2 Activitymentioning
confidence: 84%
“…Sln1 is a histidine kinase similar to those in bacterial two-component signaling systems, and its inactivation, as occurs during hyperosmotic shock, leads to activation of the Hog1 MAPK (Saito and Posas 2012). In a global screen of the Saccharomyces cerevisiae kinome, we found that, like a tor2 ts mutant (Leskoske et al 2017), when a sln1 ts mutant was shifted to the restrictive temperature, there was a dramatic loss of TORC2-dependent Ypk1 phosphorylation (Supplemental Fig. S2A) that was accompanied by hyperphosphorylation of Avo2 (Supplemental Fig.…”
Section: Torc2 Is Down-regulated During Sustained Sln1 Inactivationmentioning
confidence: 94%
“…TORC2 phosphorylates Ypk1 at multiple sites at its C-terminal end, thereby stimulating its activity [ 22 , 24 , 39 ]. Ypk1 is a member of the sub-family of eukaryotic protein kinases first defined by the related protein kinases cyclic-3’5’-AMP-dependent protein kinase (PKA), cyclic-3’5’-GMP-dependent protein kinase (PKG), and the conventional Ca 2+ -, DAG-, and PtdSer-activated protein kinases (PKC) (AGC-family of protein kinases) [ 40 , 41 ].…”
Section: Torc2 Effectorsmentioning
confidence: 99%
“…TORC1 is required for the expression of Pma1 protein and the full activity of the proton pump to resist pH stress (5). TORC2 phosphorylates and stimulates the downstream protein kinase Ypk1/ Ypk2 to regulate membrane lipids and proteins (26,27). In addition, the Snf1 pathway is involved in regulation of cell membrane biosynthesis, given that deletion of the subunits of the SNF1 complex resulted in hypersensitivity to cell membrane stress (28,29).…”
mentioning
confidence: 99%